MYC/MAX-Activated LINC00958 Promotes Lung Adenocarcinoma by Oncogenic Transcriptional Reprogramming Through HOXA1 Activation - Zhang, Tao; Su, Fei; Lu, Yong-bin; Ling, Xiao-ling; Dai, Huan-yu; Yang, Tian-ning; Zhang, Bin; Zhao, Da; Hou, Xiao-ming (Frontiers in Oncology, 2022)
Background: Lung adenocarcinoma (LUAD) is the most common histological subtype of lung cancer. The role of the long non-coding RNA (lncRNA) LINC00958, which regulates the malignant behavior of multiple tumors, in LUAD has not been elucidated. Methods: Tissue microarray, FISH, and qRT-PCR were used to detect the expression of LINC00958. Plasmid and viral infections were used to manipulate gene expression. The role of LINC00958 in LUAD was studied by cell proliferation analysis, cell apoptosis analysis, cell migration and invasion analysis, and subcutaneous inoculation of animal models. At the same time, RNA-Seq, RNA pull-down, ChIRP, ChIP, and luciferase reporter gene assays were performed to clarify the mechanism. Results: The expression of LINC00958 in LUAD tissues was significantly upregulated when compared with that in adjacent tissues and could independently predict poor survival of patients with LUAD. LINC00958 knockdown significantly inhibited the growth and metastasis of lung cancer cells in vitro and in vivo. LINC00958 localized to the nucleus, regulated oncogenes and metabolism-related and immune response-related genes, and interacted with histones. The targets of LINC00958 were TRPV3, STAP2, and EDN2 promoters with motifs of HOXA1, NANOG, FOSL2, JUN, and ATF4. Moreover, HOXA1 overexpression mitigated the LINC00958 knockdown-induced oncogenic phenotype. MYC/MAX motif, which was detected at the cis-element of LINC00958, trans-activated the LINC00958 promoter. Conclusions: MYC/MAX-trans-activated LINC00958 promotes the malignant behavior of LUAD by recruiting HOXA1 and inducing oncogenic reprogramming.